Strategi Transformatif Pimpinan Pesantren Jamiah Al-Aziziyah Dalam Meningkatkan Jumlah Santri di Era Globalisasi Pendidikan - Muhammad Reza; Muhammad Shiddiq Al Ghifari (Yayasan Madinah Al-Aziziyah, 2026)
The globalization of education presents complex challenges for Islamic educational institutions, including Islamic boarding schools (pesantren). Social changes, technological advancements, and increasing public expectations regarding educational quality demand adaptive and transformative leadership. This study aims to analyze the transformative strategies implemented by the leadership of Jamiah Al Aziziyah Islamic Boarding School in increasing the number of students (santri) in the era of educational globalization.The research employs a qualitative approach using a case study method. Data were collected through interviews, observations, and documentation, and then analyzed descriptively and analytically. The findings indicate that the increase in the number of santri was achieved through strengthening the institutional vision, implementing an integrated curriculum innovation, digitalizing promotional strategies, improving the quality of human resources, and introducing a social policy that provides a 50% registration fee reduction for victims of hydrometeorological floods. These strategies not only contributed to a quantitative increase in student enrollment but also strengthened the pesantren’s image as an inclusive Islamic educational institution that is responsive to social realities.